Impact of V-ets Erythroblastosis Virus E26 Oncogene Homolog 1 Gene Polymorphisms Upon Susceptibility to Autoimmune Diseases: A Meta-Analysis. Issue 22 (June 2015) - Zhou, Ye; Liu, Miao; Li, Jun; Hashmi, Fiza; Mao, Zhi; Zhang, Ning; Zhou, Liang; Lv, Weiran; Zheng, Jingwei; Nie, Xiaoli; Li, Changzheng
Abstract : Abstract: V-ets erythroblastosis virus E26 oncogene homolog 1 ( ETS1 ) is recognized as a gene of risk to autoimmune diseases (ADs). Two single nucleotide polymorphisms (SNPs) in ETS1 (rs1128334 G>A and rs10893872 T>C) were considered associated with ADs risk. However, the results remain conflicting. We performed a meta-analysis to evaluate more precise estimations of any relationship. We searched PubMed, OvidSP, and Chinese National Knowledge Infrastructure databases (papers published prior to September 12, 2014) and extracted data from eligible studies. Meta-analysis was performed using the STATA 12.0 software. Random effect model or fixed effect model were chosen according to the study heterogeneities. A total of 11 studies including 7359 cases (9660 controls) for rs1128334 and 8 studies including 5419 cases (7122 controls) for rs10893872 were involved in this meta-analysis. Overall, our results showed that there were significant associations for rs1128334 with AD risk in 5 genetic models, both in pooled analysis and in systemic lupus erythematous (SLE) subgroup, and in 3 genetic models of the uveitis subgroup. Although for rs10893872, the results showed that there were significant associations in allele model both in pooled analysis and in SLE subgroup. As a conclusion, this meta-analysis demonstrated that these 2 SNPs (rs1128334 and rs10893872) in ETS1 were associated with ADs risk. Abstract : Supplemental Digital Content is available in the text